Human adenovirus early region 4 open reading frame 1 genes encode growth-transforming proteins that may be distantly related to dUTP pyrophosphatase enzymes. - Weiss, R S (1997)
An essential oncogenic determinant of subgroup D human adenovirus type 9 (Ad9), which uniquely elicits estrogen-dependent mammary tumors in rats, is encoded by early region 4 open reading frame 1 (E4 ORF1). Whereas Ad9 E4 ORF1 efficiently induces transformed foci on the established rat embryo fibroblast cell line CREF, the related subgroup A Ad12 and subgroup C Ad5 E4 ORF1s do not (R. T. Javier, J. Virol. 68:3917-3924, 1994). In this study, we found that the lack of transforming activity associated with non-subgroup D adenovirus E4 ORF1s in CREF cells correlated with significantly reduced protein levels compared to Ad9 E4 ORF1 in these cells. In the human cell line TE85, however, the non-subgroup D adenovirus E4 ORF1s produced protein levels higher than those seen in CREF cells as well as transforming activities similar to that of Ad9 E4 ORF1, suggesting that all adenovirus E4 ORF1 polypeptides possess comparable cellular growth-transforming activities. In addition, searches for known proteins related to these novel viral transforming proteins revealed that the E4 ORF1 proteins had weak sequence similarity, over the entire length of the E4 ORF1 polypeptides, with a variety of organismal and viral dUTP pyrophosphatase (dUTPase) enzymes. Even though adenovirus E4 ORF1 proteins lacked conserved protein motifs of dUTPase enzymes or detectable enzymatic activity, E4 ORF1 and dUTPase proteins were predicted to possess strikingly similar secondary structure arrangements. It was also established that an avian adenovirus protein, encoded within a genomic location analogous to that of the human adenovirus E4 ORF1s, was a genuine dUTPase enzyme. Although no functional similarity was found for the E4 ORF1 and dUTPase proteins, we propose that human adenovirus E4 ORF1 genes have evolved from an ancestral adenovirus dUTPase and, from this structural framework, developed novel transforming properties.